Profits: The Views of Jerome Levy and Michal Kalecki - S. Jay Levy (Levy Economics Institute of Bard College, 2000)
Profits are the incentive for production and therefore employment in almost all of the world's economies; they also may represent exploitation of workers and consumers. Jerome Levy, using a complex process, derived the profits identity during the years 1908-1914. Michal Kalecki, taking advantage of the development of national accounting, derived it in the 1930s. Levy viewed the equation as a tool for developing policies that would enable capitalist economies to achieve high rates of employment. Recent American experience gives weight to his views. Kalecki's insights from the identity strengthened his belief that unemployment was inescapable under capitalism. He would find empirical support in Europe's high unemployment rates during the past two decades.
Keywords: 330